Gift or gamble? Evaluating the impact of urban low-carbon governance on high-quality development in China - Yang, Shunqing; Zhou, Yingying; Meng, Qingxuan (Frontiers in Environmental Science, 2025)
IntroductionClimate change demands urgent action, and low-carbon urban governance has become crucial for sustainable development. China introduced the Low-Carbon City Pilot (LCCP) policy to reduce emissions and promote green growth. This study evaluates how LCCP affects high-quality development (HQD), providing insights for policymakers.MethodsWe measured HQD using the entropy weight method and employed the difference-in-differences (DID) approach with 2000-2021 panel data from 351 Chinese cities, treating the LCCP as a quasi-natural experiment. Analyses included baseline tests, robustness tests, mechanism tests, and heterogeneity analysis.ResultsThe findings indicate that the LCCP significantly enhances HQD, thereby supporting the Porter Hypothesis within the context of China’s environmental and economic policies. Robustness tests, including parallel trend test, propensity score matching-DID, expanded sample analysis and substituted the explained variable, confirm the reliability of these results. Mechanism analysis reveals that the improvements in HQD are driven by technological innovation, industrial upgrading, infrastructure development, and energy system transformation. Furthermore, heterogeneity analysis shows that the policy’s impact is more pronounced in general cities and Han Chinese provinces.DiscussionThese results demonstrate that the LCCP functions as a “gift” for enhancing HQD, offering valuable insights for refining low-carbon governance policies and providing actionable lessons for other countries pursuing ecological environment with well-being growth.